Результати хірургічного лікування спорадичного та спадкового медулярного раку щитоподібної залози у віддалений післяопераційний період - Ларін, О. С.; Нечай, О. П.; Черенько, С. М. (Clinical Endocrinology and Endocrine Surgery, 2008)
Performed study analyzes the remote results of surgical treatment of medullar carcinoma. Thus, results of surgical treatment of patients with inherited form are much worse than in those with sporadic form of medullar carcinoma. Recovery or remission were registered in 52,94% and 72,72% accordingly. Relapse in form of regional metastases — in 17,64% and 9,09%, remote metastases were revealed in 29,41% and 18,18% of cases accordingly (p<0,05).